2009
DOI: 10.1093/cvr/cvp091
|View full text |Cite
|
Sign up to set email alerts
|

Valsartan regulates the interaction of angiotensin II type 1 receptor and endothelial nitric oxide synthase via Src/PI3K/Akt signalling

Abstract: Valsartan-induced NO production in ECs is mediated through Src/PI3K/Akt-dependent phosphorylation of eNOS. Valsartan-induced AT1R phosphorylation depends on Src but not PI3K, whereas valsartan-induced suppression of AT1R-eNOS interaction depends on Src/PI3K/Akt signalling. These results indicate a novel vasoprotective mechanism of valsartan in upregulating NO production in ECs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 36 publications
0
40
1
Order By: Relevance
“…Activation of eNOS‐NO signaling is suggested to be a major mechanism of clinical therapeutic drugs in treating cardiovascular diseases 26, 27, 28. eNOS can be activated by physiological and metabolic stimuli, such as shear stress and clinical therapeutic drugs, and result in NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of eNOS‐NO signaling is suggested to be a major mechanism of clinical therapeutic drugs in treating cardiovascular diseases 26, 27, 28. eNOS can be activated by physiological and metabolic stimuli, such as shear stress and clinical therapeutic drugs, and result in NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Losartan increases eNOS phosphorylation in the rat heart [10]. In human aortic endothelial cells, valsartan induced eNOS phosphorylation is dependent on PI3K, but not on protein kinase A (PKA), protein kinase C (PKC) or adenosine monophosphate-activated protein kinase (AMPK) [35]. ARBs prevent NOS uncoupling and the production of superoxide, increasing NO availability [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that azilsartan (TAK-491) reduced IS and increased Akt phosphorylation following ischemiareperfusion in non-diabetic rats [18]. Previous studies have also shown that ARBs increase Akt phosphorylation [27,[54][55][56] and several studies have shown that AL increases Akt phosphorylation in various experimental models [52,[57][58][59][60]. Thus, increased phosphorylation of Akt may mediate the protective effects of VA and AL against ischemia-reperfusion injury.…”
Section: Akt Phosphorylationmentioning
confidence: 94%
“…Losartan also increases eNOS phosphorylation in the rat heart [64]. In human aortic endothelial cells, valsartan induced eNOS phosphorylation is dependent on PI3K, but not on protein kinase A (PKA), protein kinase C (PKC) or adenosine monophosphate-activated protein kinase (AMPK) [54]. ARBs prevent NOS uncoupling and the production of superoxide, increasing NO availability [65].…”
Section: Akt Phosphorylationmentioning
confidence: 99%